Premix Flour for Preparation of Empek-Empek Based on Surimi Technology. (November 2019) - Tawali, AB; Manggabarani, S; Ramli, AR; Sirajuddin, S; Made, S; Mahendradatta, M
Abstract: Empek-empek is one of signatured food from Indonesia which made from fish paste, tapioca starch, and other additional ingredients. The objective of this present work was to develop premix flour for making empek-empek using mackerel surimi and to evaluate their chemical characteristic and sensory attributes of the product. The mackerel fish was made into surimi, powdered, then mixed with tapioca starch and other additional ingredients. The following aspect were characterized including moisture, fat, protein, ash, carbohydrate content, and sensory acceptability of the premix product. The results showed that mackerel surimi flour at level of 66, 67% is the recommended formula. The empek-empek which made from this premix flour presented hedonic score "like" for color and "like moderately" for aroma, texture and flavor. In conclusion, our premix can be used for preparing empek-empek with less complicated process and the product did not have any negative results on sensory acceptability.